Nasionalisme, Demokratisasi, dan Sentimen Primordialisme di Indonesia: Problematika Identitas Keetnisan Versus Keindonesiaan (Studi Kasus Aceh, Papua, Bali, dan Riau) - Noor, Firman (Jurnal Penelitian Politik, 2016)
This research explores theoretically the reasons behind the emergence of primordial sentiment in Indonesia in the era of democratization The research indicates six factors that determine this phenomenon namely the continuation of incorrect interpretation about the true meaning of Indonesia the existence of formalistic understanding on the role of religion in the state economical disparity political injustice and state domination in interpreting national symbols In this regards the research finds that mismanage in governing people and the repressive tendency of previous government as the trigger of the emergence of primordial sentiment in reformasi era.